The relationship between Comprehensive Geriatric Assessment parameters and depression in elderly patients - Ju, Yanmin; Liu, Ting; Zhang, Kexin; Lin, Xiaoye; Zheng, Enlai; Leng, Jiyan (Frontiers in Aging Neuroscience, 2022)
Methods: A cross-sectional study of 211 outpatients and inpatients aged ≥ 65 from the Comprehensive Geriatric Assessment database was conducted. A Comprehensive Geriatric Assessment inventory was prepared by compiling and screening general characteristics, chronic diseases (cardiovascular disease, diabetes, peptic ulcer disease), nutritional status, daily living ability, anthropometric measurements (body mass index, upper arm circumference, calf circumference), and blood biochemical indicators (hemoglobin, albumin, prealbumin, triglycerides, and low-density lipoprotein cholesterol). The Geriatric Depression Scale was also conducted for each elderly patient to screen for depression. Multivariable logistic regression analysis was used to determine the association between the parameters of Comprehensive Geriatric Assessment and geriatric depression. Result: There were 63 patients in the depression group with a median age of 84.00 years, and 148 patients in the non-depression group with a median age of 78.50 years. After controlling for confounders,the risk of depression in elderly patients with cardiovascular diseases was 6.011 times higher than that in those without cardiovascular diseases (P < 0.001); and the risk of depression in elderly patients with peptic ulcer diseases was 4.352 times higher than that in those without peptic ulcer diseases (P < 0.001); the risk of depression in elderly patients decreased by 22.6% for each 1-point increase in Mini Nutritional Assessment (P < 0.001). The risk of depression in elderly patients decreased by 19.9% for each 1-point increase in calf circumference (P = 0.002), and by 13.0% for each 1-point increase in albumin (P = 0.014).